Design, develop, and implement the strategic information system on health, dependence, and healthy aging: an analysis of the Mexican experience - Luis Miguel Gutierrez-Robledo; Rosa Estela García-Chanes; Emely Estefanía Max-Monroy; Liliana Giraldo-Rodríguez; Teresa Álvarez-Cisneros; Ana Cristina Gómez-Ugarte; José Antonio de la Rosa-Parra; Ángel Gabriel Estévez-Pedraza; Fernando Rebollar-Castelán; Víctor Montaño-Serrano; Francisco Gerson Cuero-Muciño; Roberto Carlos Rivera-González; et al. (BMC, 2024)
Abstract Background The Decade of Healthy Aging (2021-2030) emerges as a 10 years strategy to improve the lives of older adults, their families, and the communities in which they live. One of the actions defined in this framework is related to improving the measurement, monitoring, and understanding of characteristics, factors, and needs related to aging and health. The aim was to analyze and assess the process of construction and development of the Strategic Information System on Health, Funcional Dependence and Aging (SIESDE, for its acronym in Spanish). SIESDE will provide strategic information in Mexico at the municipal, state, and national levels that support the public policies on healthy aging. Methods The system processes and analyzes the data sources of the Health Information Systems and the National System of Statistical and Geographical Information. SIESDE comprises three components: (1) Design, construction, and evaluation of the indicators; (2) storage, management, and visualization, and (3) diffusion and translation of information. Results A total of 135 indicators were built on seven themes: (1) demographic, socioeconomic, and aging conditions, (2) health, (3) functional dependence, (4) healthy aging, (5) health services, (6) social and physical environments, and (7) complex indicators. Conclusions SIESDE is an effective system for providing an overall view of health, aging, and functional dependence.